Successful Balloon Assisted Percutaneous Thrombin Injection of Right Subclavian Artery Pseudoaneurysm. Issue 5 (September 2017) - Brown, Andrew D.; Hirpara, Dhruvin H.; Jaberi, Arash; Oreopoulos, George D.; Simons, Martin E.
Purpose: To report the use of a balloon catheter to facilitate percutaneous ultrasound-guided thrombin injection of a subclavian artery pseudoaneurysm. Case report: A 36-year-old man presented with hoarseness after the insertion of a right temporary internal jugular line. Arteriography showed a short neck right subclavian artery pseudoaneurysm. A 6 mm × 40 mm balloon catheter was positioned across the neck of the pseudoaneurysm to permit percutaneous ultrasound-guided thrombin injection. Immediate post-treatment angiogram demonstrated no filling of the pseudoaneurysm. Seven-month clinical and imaging follow-up confirmed resolution of the pseudoaneurysm and hoarseness. Conclusions: This clinical vignette highlights the potential of balloon catheter-assisted percutaneous ultrasound-guided thrombin injection as an alternative to open or endovascular repair of pseudoaneurysms of the subclavian arteries.